2007
DOI: 10.1038/sj.onc.1210591
|View full text |Cite
|
Sign up to set email alerts
|

RET(MEN 2B) is active in the endoplasmic reticulum before reaching the cell surface

Abstract: MEN 2B (multiple endocrine neoplasia type 2B) is an autosomal dominant cancer syndrome caused by an oncogenic form of the receptor tyrosine kinase REarranged during transfection (RET). The MEN 2B syndrome is associated with an abnormal autophosphorylation of the mutated receptor even without ligand-stimulation. Here, we characterize the activation of a RET MEN 2B variant carrying the point mutation Met918Thr, and show that the 150 kDa precursor of RET MEN 2B becomes phosphorylated already during synthesis in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…It is known that the endoplasmic reticulum links to adaptor proteins, to influence RET function in different directions. For example, in MEN2B, a RET 150-kDa precursor has been shown to be phosphorylated during its synthesis in the endoplasmic reticulum from which it induces downstream signaling and activation [28]. The endoplasmic reticulum has also been shown to decrease cell surface RET expression in HSCR [29].…”
Section: Discussionmentioning
confidence: 98%
“…It is known that the endoplasmic reticulum links to adaptor proteins, to influence RET function in different directions. For example, in MEN2B, a RET 150-kDa precursor has been shown to be phosphorylated during its synthesis in the endoplasmic reticulum from which it induces downstream signaling and activation [28]. The endoplasmic reticulum has also been shown to decrease cell surface RET expression in HSCR [29].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it has been assumed that D1246N and M1268T mutants are oncogenic simply because they are highly activated 27,40 . Recent studies however have reported signalling of mutated activated RTKs, in an immature form, from intracellular compartments of the secretory pathway [41][42][43][44] , leading to tumorigenesis 41,45 . We suggest that Met mutants D1246N and M1268T are oncogenic not only because they are activated but also because they signal on endosomes.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, the mutated RET no longer requires dimerization to become active [37]. In a recent study, it was shown that codon 918 RET mutant (MEN 2B) is already active in the endoplasmic reticulum where it interacts with adaptor proteins [38]. Interestingly, several types of RET mutation can be further activated by GDNF as well [39].…”
Section: Molecular Biology Of Mtc and The Ret Proto-oncogenementioning
confidence: 99%